Firm heterogeneity and choice of ownership structure: an empirical analysis of German FDI in India - Holger Görg; Verena Lauber; Birgit Meyer; Peter Nunnenkamp (Kiel Institute for the World Economy (IfW), 2008)
We contribute to the nascent literature on the heterogeneity of multinational enterprises (MNEs) and the relevance of firm characteristics for analyzing the determinants of outward foreign direct investment (FDI). The focus is on the role of firm-level heterogeneity when MNEs decide on the share of ownership in foreign affiliates. We combine two firm-specific datasets on German MNEs with varying equity stakes in Indian affiliates. The impact of firm characteristics on ownership shares is assessed in the context of OLS and fractional logit models, controlling for industry and location characteristics. We show that the effect of several characteristics differs between the establishment of new affiliates by German MNEs and their engagement in already existing Indian firms. Most notably, the productivity of the German parents matters only for ownership shares in new affiliates.
Keywords: F23; L25; 330; Multinational enterprises; firm characteristics; Indian locations; German FDI; ownership share; Direktinvestition; Deutsch; Multinationales Unternehmen; Eigentümerstruktur; Produktivität; Schätzung; Deutschland; Indien